▼Ivabradine for stable angina?. Issue 11 (5th November 2008) - Unknown
Abstract : Up to 1 in 25 people in Europe and the USA have stable angina, with symptoms that may limit function and quality of life.1, 2 Beta-blockers are usually used in initial symptomatic treatment, but may cause unwanted effects.3 – 6 They are also contraindicated in some patients (e.g. those with uncontrolled heart failure, severe peripheral vascular disease) and should be avoided in patients with asthma or a history of reversible obstructive airways disease or bronchospasm.6 ▼Ivabradine (Procoralan – Servier) is the first in a new class of specific heart rate-reducing drugs and is licensed for the "symptomatic treatment of chronic stable angina pectoris in patients with normal sinus rhythm, who have a contra-indication or intolerance for beta-blockers".7, 8 Here we consider the place of ivabradine in the management of patients with stable angina.